A lexicon of the Homeric dialect - Cunliffe, Richard John (Norman University of Oklahoma Press, 1963)
The Lexicon gives students the help they need to read Homer extensively, with pleasure , and with the fewist possible obsticles.
English and Homeric Greek text.
Keywords: Homer -- Language -- Glossaries, etc; Homer -- Dictionaries; Greek language -- Glossaries, vocabularies, etc; Greek language -- Dictionaries -- English; English language -- Dictionaries -- Greek